Antiviral drug profile of seasonal influenza viruses circulating in Portugal from 2004/2005 to 2008/2009 winter season - Correia, Vanessa (2013)
A research project on antiviral drug resistance of influenza viruses circulating in Portugal has been carried out since 2007. Here, the first results obtained regarding the evaluation of susceptibility to amantadine and oseltamivir are presented. Information about antiviral prescription and exposure was available through the National Influenza Surveillance Programme. Amantadine susceptibility was evaluated by pyrosequencing for known resistance markers on 178 influenza A strains from 2004/2005 to 2006/2007. Susceptibility to oseltamivir was evaluated by 50% inhibitory concentration determination on 340 virus strains from 2004/2005 to 2008/2009, 134 of which were further analyzed by sequencing of the neuraminidase gene. This study revealed that influenza antiviral drugs were rarely prescribed at national level. Resistance to amantadine was observed on only A(H3N2) strain isolated during 2005/2006 and on 38 (74.5%) of the 51 A(H3N2) strains from 2006/2007, all carrying the mutation S31N in theirM2sequence. Oseltamivir resistance was observed in 6 (20.7%) of the 29 A(H1N1) strains from 2007/2008 and in all strains from 2008/2009, which exhibited extremely high IC50 values and carrying the mutation H275Y in their neuraminidase sequence. The national data generated and analyzed in this study may contribute to increase the knowledge on influenza antiviral drug resistance which is a problem of global concern.